A Novel on the Borderline of Literary Traditions:The Narrative Innovations of Leslie Marmon Silko’s Ceremony - Mudriczki, Judit (FOCUS: Papers in English Literary and Cultural Studies, 2006)
"One of the things I hope you would have in approaching Ceremony, or any other pieces that are consciously working with an American English and an American experience and American personae and struggles, is that openness, to realize that you’re going to see different structures and different emphases." — Leslie Marmon Silko, “Teller of Stories” Although there are certain similarities between the narrative technique of Ceremony and other twentieth century novels, especially those of William Faulkner, for a long time Leslie Marmon Silko’s work did not seem to fit perfectly into the American literary canon (Work and Cowell 43). The unusual structure of the book, which juxtaposes a narrative storyline and passages of poetry that break the flow of prose and imply different narrative voices and shifting points of view, has already challenged many scholars trying to interpret the story within the framework of a traditional critical approach. As Gregory Salyer rightly put it: “Much more than a shattered narrative line, this novel is a spider web of interconnecting stories, themes, and events, and any attempt to straighten out these lines is bound to fail, to break the web”.